Association between major dietary patterns and obesity phenotypes in southwest China: baseline survey results from Hechuan - Shaomei, Wang; Dezhi, Jing; Mengfen, Li; Huaan, Duan; Xianbin, Ding; Juan, Peng; Xia, Li; Yanfeng, Zhu (Frontiers in Nutrition, 2024)
In order to identify the main dietary patterns in Hechuan and clarify how they are associated with obesity phenotypes.A cross-sectional study was conducted based on the baseline survey of a general population cohort study in Southwest China. A semi-quantitative food frequency questionnaire was used to investigate dietary habits of the subjects in the past year. Principal component analysis was used to identify the main dietary patterns, and multinomial logistic regression analysis was used to describe the association of major dietary patterns and obesity phenotypes.Results: Three major dietary patterns were identified. The subjects followed the wheaten food dietary pattern had a higher likelihood having MHO (OR 1.05, 95%CI 1.02-1.08), MUNW (OR 1.08, 95%CI 1.00-1.16) and MUO (OR 1.07, 95%CI 1.04-1.11). Specifically, those with the highest wheaten food dietary pattern were 1.60 times more likely to have MHO (OR 1.60, 95%CI 1.25-2.05), 2.62 times more likely to have MUNW (OR 2.62, 95%CI 1.28-5.37) and 2.01 times more likely to have MUO (OR 2.01,95%CI 1.51-2.69) than those with the lowest wheaten food pattern.Conclusions: wheaten food dietary pattern may increase the risk of obesity and metabolic abnormalities, and timely intervention should be carried out for this group of people.